The Prosthetic Management of a Case of Epulis Fissuratum by a Novel Technique - Mekayssi, Rabia; Taleb, Bouchra; Merzouk, Nadia; Benfdil, Faîza (Odovtos - International Journal of Dental Sciences, 2020)
The clinical management of the epulis involves the elimination of causal factors, excision of fibrous tissue excess accompanied by an appropriate prosthetic rehabilitation. The confection of interim prosthesis or the rectification of old prosthesis for the setting up of a tissue conditioner if necessary, to improve the healing and prevent the decrease of the vestibule depth after the surgical exeresis. Throughout this paper, we are going to present a new technique for the correction of old prostheses poorly adapted for the management of a case of the epulis fissuratum.